Immunosuppression in trypanotolerant N'Dama cattle following Trypanosoma congolense infection - Flynn, J.N.; Sileghem, M.R. (Wiley, 1993)
Tsetse‐transmitted Trypanosoma congolense infection causes an impairment of in vitro T cell proliferative responses in Boran (Bos indicus) cattle. To assess the importance of this phenomenon as it may relate to the ability of trypanotolerant cattle to control infection with trypanosomes, T cell proliferative responses to mitogenic stimulus with Concanavalin A were measured in N'Dama (Bos taurus,) cattle throughout infection. The responses of peripheral blood mononuclear cells from Boran and N'Dama cattle were similar. Depressed proliferative responses were observed with cells of both breeds at 12 days post infection, after which the responses returned to levels similar to those recorded pre‐infection. Immunosuppression was also studied in the lymph nodes of a major histocompa‐tibility complex (MHC)‐matched pair of N'Dama cattle. Lymph node cells from the infected animal failed to respond to mitogenic stimulus. Co‐culture experiments in which the cells from this node were mixed with either lymph node cells or peripheral blood mononuclear cells from the non‐infected MHC‐compatible animal revealed the presence of suppressor cells, acting in a prostaglandin‐independent manner, capable of arresting mitogen‐induced T cell proliferation.